There is Science at Guadalupe - Figueiredo, S. (Open Schools Journal for Open Science, 2020)
Our project seeks to disseminate science throughout the school community. 12th-grade students are building a scientific magazine and developing mini-projects, in small groups, which aim to stimulate the school community’s interest in science and scientific discoveries. There are groups of students doing research and planning experiments. Other groups have established partnerships with pre-school and 1st cycle classes so that, in a playful and fun way, interest in science grows more and earlier. The project started in October/November 2019 and, at this moment, we are still planning and devising strategies. In parallel, some of the mini-projects are already being implemented. In partnerships with the pre-school and 1st cycle classes, we have already started a scientific cooking project. We will also hold workshops on building terrariums, maintaining aquariums, and composting projects.